Управление рисками в долгосрочном страховании жизни (Путеводитель предпринимателя)
The research problem is caused by necessity of introduction of scientific management methods investment risks in the life insurance companies in the Russian market for decision-making optimization on placing of means of insurance reserves, in view of the restrictions set by accepted obligations of the insurer, and the existing standard base regulating investment activity of insurers.